147k views
5 votes
Which shows 60^2 − 40^2 being evaluated using the difference of squares method?

A. 60^2 − 40^2 = (3600 + 1600)(3600 − 1600) = 10,400,000

B. 60^2 − 40^2 = 3600 − 1600 = 2,000

C. 60^2 − 40^2 = (60 − 40)^2 = 20^2 = 400

D. 60^2 − 40^2 = (60 + 40)(60 − 40) = (100)(20) = 2,000

User Qwabra
by
5.3k points

2 Answers

4 votes

Answer:

D. 60^2 − 40^2 = (60 + 40)(60 − 40) = (100)(20) = 2,000

Explanation:

User Kockiren
by
5.4k points
0 votes
The difference of squares method uses the following formula:


a^(2) - b^(2) = (a+b)(a-b)

Answer A has the squares multiplied out, then put into the formula, which is incorrect.

Answer B does not use this formula, as the squares are multiplied out and solved without using this method.

Answer C subtracts in terms of the power, which is completely wrong.

The answer is D.
User Gregghz
by
5.4k points